Rhytidectomy: Analysis of Videos Available Online - Nissan, Michael E.; Gupta, Amar; Carron, Joey; Rayess, Hani; Carron, Michael (Facial Plastic Surgery, 2017)
The objective of this study was to examine YouTube videos related to rhytidectomy created by both physicians and nonphysicians to determine the content of the videos, the selected topics of discussion, and other important parameters using a cross-sectional analysis study design. A YouTube search result for the keyword “facelift” was performed. Videos pertaining to the rhytidectomy procedure were included in this analysis. Authorship, length of video, primary objective, and total views were recorded. Total 80 videos (81%) were authored by physicians, 14 (14%) were authored by patients, and 5 (5%) were authored by a third party. Fifty-eight (59%) videos were shorter than 5 minutes, and 41 videos (41%) were longer than 5 minutes. Fifty-two (53%) videos were viewed fewer than 10,000 times, and 47 videos (47%) were viewed more than 10,000 times. Forty (40%) videos had a primary objective of providing information, 13 (13%) had a primary objective of providing the patient's perspective, and 46 (46%) had a primary objective of advertising a physician's practice. A chi-square test for independence with threshold of significance < 0.05 was used to compare whether or not the primary objective of the videos depended on the type of authorship. A significant difference was found between physician- and patient-authored videos. In addition, the 12 (12%) videos with the most views of videos included in this study were responsible for 75% of the total views of videos included in this study. Advertising was a goal of both physician- and patient-based videos, but physician-based videos were more likely to provide information about the procedure whereas patient-based videos more commonly presented a patient's personal perspective. The most popular 12% of videos were responsible for 75% of total views in this analysis, indicating that a small minority of perspectives dominates the YouTube viewership regarding rhytidectomy. The general public may be misled by information found by viewing these videos as the Internet generally lacks safeguards for quality or accuracy. It may be prudent for academic or professional organizations to provide videos intended to achieve a more neutral, well-informed perspective.
Keywords: facelift; face lift; rhytidectomy; patient education; patient education materials; YouTube